2011
DOI: 10.1103/physrevb.84.205452
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effects on chemisorption properties: CO on ultrathin Cu films from first principles

Abstract: We address, by means of ab-initio calculations, the origin of the correlation that has been observed experimentally between the chemisorption energy of CO on nanoscale Cu(001) supported films and quantum-size effects. The calculated chemisorption energy shows systematic oscillations, as a function of film thickness, with a periodicity corresponding to that of quantum-well states at Γ crossing the Fermi energy. We explain this trend based on the oscillations, with film thickness, of the decay length on the vacu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We found that the E ads values oscillate with slab thickness from three to seven layers with a period of two layers, but the thickness dependence is almost negligible for slabs with more than eight layers. This oscillatory behavior is attributed to the quantum size effect of the thin Cu(111) slab used. In the following, we report the results calculated with eight-layer slabs.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the E ads values oscillate with slab thickness from three to seven layers with a period of two layers, but the thickness dependence is almost negligible for slabs with more than eight layers. This oscillatory behavior is attributed to the quantum size effect of the thin Cu(111) slab used. In the following, we report the results calculated with eight-layer slabs.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of such an enhancement, and especially its sensitive coverage dependence, has not been investigated or understood, although it was speculated that quantum well states (QWS) of the alkali metal overlayers might be responsible for the enhanced water splitting reaction. Actually, it was found that the thin-film QWS play important roles in the thickness-dependent variations of the adsorption energy and surface reactivity for molecules and atoms on metal thin films. Both the magnitude ,, and the decay length ,, of the electronic density of states of the film at the Fermi level have been proposed to be responsible for these quantum size effects.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it was found that the thin-film QWS play important roles in the thicknessdependent variations of the adsorption energy and surface reactivity for molecules and atoms on metal thin films. 39−47 Both the magnitude 39,41,45 and the decay length 40,43,47 of the electronic density of states of the film at the Fermi level have been proposed to be responsible for these quantum size effects.…”
Section: ■ Introductionmentioning
confidence: 99%